Analisis Faktor-Faktor Yang Mempengaruhi Keberhasilan Usaha Pada Industri Kripik Tempe di Desa Sadang Ngawi - Arsiati Arsiati; Ruslina Yulaika (Universitas PGRI Madiun, 2021)
These research aim to know the influence of the factors analysis that influence the successful of work “Kripik Tempe Industry” in Sadang village Ngawi. In this research we use the survey research method and the data collecting technigue, that use the questionare, observation, interview and the library study. As a sample from this research, we use the tempe kripik industry all in Sadang Ngawi there are 87 people in here. We use a double regression method. From the result of research, variable X1 (financial capital), variable X2 (experience), variable X3(promotion), variable X4 (work capability). Partially, it influence to variable Y ( work succesfull). Score t from variables respectively. As far the score t from variables respecttively: Variable Capital business (X1) we get t : 3.036, business experience (X2) we get t : 3.166, promotion (X3) : 3.647 and score t from business capability: 4.235.The result from the test F : from the four variables influence to the succesfull of work simultanly, score F :20.714 is on P < 0,05. From the result of coefisience determination, we know that the successfull of work is influenced by bussiness capital (X1), work experience (X2), promotion (X3) and the work capability (x4) : 0,503 or 50.30 %, and rest of effort 0.497 or 49.70 %. they are influenced by the other variable that it is not in this research